Perlindungan Bagi Hak Kekayaan Intelektual Komunal - Yunita Maya Putri (Fakultas Hukum Universitas Djuanda Bogor, 2021)
Protection of communal intellectual property rights is very important in Indonesia. Because communal intellectual property rights are not based on a